Digital competencies in teachers and students during the pandemic: a systematic review - Criado Davila, Yvette Vanessa; Muñoz Ccuro, Felipa Elvira; Arce Vizcarra, Fernando Guillermo; Maldonado Cueva, Percy David; San Miguel Velásquez, Yuly Victoria (LACCEI, 2025)
The pandemic generated by the COVID 19, led to a series of demands at the educational level, especially those related to the digital competencies of teachers and students necessary for the teaching-learning process. The general objective of this research was to analyze the studies conducted regarding digital competencies in teachers and students during the pandemic through a systematic review. It is a basic, qualitative, phenomenological research, having as method the systematic review under the Prisma approach, using the documentary analysis technique, as well as the individual analysis matrix instrument. The population consisted of 3472 articles from the Scopus database, written in English, Spanish and Portuguese on digital competencies, digital skills or technological competencies during the years 2020 to 2023. Likewise, the total sample consisted of 82 articles and the Rayyan program was used to arrive at it. Among the results, it was found that high school teachers have higher digital competencies, and among them, female teachers have slightly higher digital competencies than male teachers. On the other hand, undergraduate students have better digital competencies. Likewise, as digital competencies favor the learning of students and teachers, that information literacy is associated with digital awareness, and that, although there are trainings for teachers and students, they are insufficient and without a previous diagnosis, since it is necessary to consider levels, previous knowledge and accompaniment. Also, in the use of digital tools, several digital resources are employed, and the use of the Flipped Classroom methodology is scarce.